Eficácia da imunoterapia no tratamento de pitiose facial em equino - Pereira dos Santos, Carlos Eduardo [UNESP]; Juliano, Raquel Soares; Santurio, Janio Morais; Marques, Luiz Carlos [UNESP] (Universidade Federal do Rio Grande do Sul (UFRGS), 2011)
Background: Pythiosis in horses is a proliferative and ulcerative disease that primarily affects the skin and subcutaneous tissue of limbs, thoracic-abdominal region and head. This disease sometimes can also affect limb bones or cause tumoral masses in abdomen. Usually, the cutaneous cases are confused with habronemiasis. The disease is more common in marshy areas, places with formation of slow drainage ponds and aquatic vegetation under high temperatures. The aim of this study was to describe the development of facial lesions in a horse caused by pythiosis in Cuiaba, Mato Grosso, and, additionally to discuss relevant issues regarding the diagnosis, clinical course and response to immunotherapy treatment.Case: One five years old mare of unknown breed, created in property located in the Cerrado region, had a wound on its face difficult to be healed and non-responsive to several treatments based on ivermectin and organophosphate administrated by either topical or systemic via. The animal was assisted on the farm of origin by the veterinary team of the Clinical Medicine sector, of the Veterinary Hospital, Universidade Federal de Mato Grosso (HOVET-UFMT). on the occasion of the visit, which occurred 60 days after onset of signs, the animal showed a circular single large lesion, ulcerative with serous discharge on the right part of its face, between the eyes and nostrils. There were some necrotic foci with sinus, from which kunkers were extracted; a condition compatible with pythiosis. The diagnosis was confirmed by histology, ELISA and PCR.Discussion: Assuming pythiosis from data obtained from the survey and profile of the lesion (secretory aspect, emaciation and presence of sinus and kunkers), immunotherapy treatment was immediately applied. The advanced clinical aspects and the fact that early diagnosis and treatment are essentials to satisfactory therapeutic response were also taken into consideration for starting the treatment. The remission of signs was achieved after five subcutaneous applications with 14 days between each application. From the second application, it was observed clinical improvement and after 60 days of treatment there was almost complete remission of signs. The signs for a satisfactory response in the injury site followed the order of decreasing secretory aspect, decreasing borders, decrease the itching and bringing the edges together with the formation of a thin layer of crust on the surface. Pythiosis cases with lesions on the face and lower abdomen are commonly confused with habronemiasis by macroscopic and widespread similarity between technicians and attendants, and essential support to the diagnosis through laboratory tests, which in turn are still underutilized. In this case, the authors demonstrated the therapeutic efficacy of immunotherapy as an advantage, considering the possibility of applying it in cases of lesions in areas of difficult surgical access, treatment conditions in the field, with low cost and ease of application. Further studies approaching this alternative therapy are necessary, since side effects have been observed in some cases.
Efficacy of Immunotherapy in the Treatment of Facial Horse Pythiosis
Keywords: pythiosis; immunotherapy; diagnosis methods